Asymmetric Hydrogenative Coupling of Indoles with Unsaturated Ketones Enabled by Copper/Ruthenium Relay Catalysis - Zhang, Jian; Guo, Chen; Tang, Weijun; Xue, Dong; Sun, Huaming; Xiao, Jianliang; Wang, Chao (Synthesis, 2024)
A relay catalytic system is developed for the asymmetric hydrogenative coupling of indoles with α,β-unsaturated ketones, affording enantioenriched chiral γ-indole alcohols with broad substrate scope and excellent enantioselectivities (32 examples, up to >99% ee). Mechanistic studies suggest that the relay catalytic system consists of copper-catalyzed alkylation and ruthenium-catalyzed asymmetric hydrogenation.
Keywords: relay catalysis; indole; unsaturated ketone; chiral alcohol; C–C bond formation